Rehabilitation of the elbow following sports injury - Ellenbecker, T. S.; Pieczynski, T. E.; Davies, G. J. (Clinics in Sports Medicine, 2010)
Evaluation of the athlete with an elbow injury involves a complete upper extremity approach and a corresponding treatment approach that addresses the identified deficiencies to restore normal function. A significant focus should be placed on the proximal aspect of the upper extremity in addition to the obvious distal injury. A detailed review of the available treatment modalities fails to identify any clear definitive choice to address pain levels; however, a combination of modalities and appropriate exercise can be used in the early rehabilitation phases. The use of a total arm strengthening program along with evaluation of the athlete's sport mechanics is required to successfully return the patient back to their preinjury level of function. A supervised interval sport return program is also a necessary component of the complete rehabilitation program for the athlete with an elbow injury.